Influence of weighted cuffs on ground reaction forces in running of an elite unilateral upper extremity amputee athlete - Litzenberger, S.; Mally, F.; Braunstein, B.; Willwacher, S.; Sabo, A.; Brüggemann, G. P. (Procedia Engineering, 2016)
Due to their opposing movement the swinging arms are considered not to have a major contribution to the overall motion of running. However, missing one upper extremity limb can lead to significant asymmetries. In the present study it was investigated what influence weighted cuffs, which are added to the missing limb, have on the ground reaction forces in running of an elite unilateral upper extremity amputee athlete. One elite athlete (PB 400m: 0:48.45, PB 800m:1:50.92) currently classified as T47 by the International Paralympic Committee due to missing his right forearm participated in this study. The subject had to perform several runs on a 100m Tartan track with a velocity of 8 m/s (high race speed) without and with wearing two differently weighted cuffs (0.5 kg and 1 kg) applied to the elbow of the impaired limb. Ground reaction forces (GRFs) were captured using four floor- level mounted Kistler force plates, mean vertical and horizontal GRFs were calculated over 100% of stance phase duration and statistical data was evaluated for maximum and minimum values. Patterns of vertical GRFs did not differ dramatically whereas the maximum vertical force revealed a highly significant and significant difference between left and right foot when running with heavy or no additional weight respectively. Overall results showed only singular differences for different weight conditions, but several statistically significant differences between left and right foot were found independent from weight conditions.